The Effect of the School Environment on Student Morality - Basmin, Brenda; Nursaeni, Nursaeni; Rahmadani, Ervi; Middin, Murdianti (South Sulawesi Education Development (SSED), 2025)
This study aims to determine the Effect of the School Environment on the morale of fifth-grade students at SDN 1 Porehu, North Kolaka Regency. Employing a quantitative ex post facto design, the research involved a saturated sample of all 26 fifth-grade students. Data were gathered through expert-validated questionnaires and analysed using descriptive statistics, product-moment correlation, and the coefficient of determination. The findings indicated that both the school environment (61.54%) and student moral character (65.38%) were categorised as good. The correlation analysis revealed a significant positive relationship between the two variables (r = 0.649, p < 0.05). Furthermore, the coefficient of determination (R² = 0.42) indicates that the school environment accounts for 42% of the variance in students' moral character, with the remaining 58% attributed to other factors. These results underscore the substantial role of the school environment in shaping student morality.